Das potencialidades de uma proposta curricular às fragilidades de um recurso didático: cadernos de apoio e aprendizagem (Língua Portuguesa) - Savioli, Marcia Regina (2013)
The choice of Education (Curriculum) as an area of knowledge is the reason intent to contribute to the training of qualified citizens for social participation. The focus in Portuguese explained by historically language teaching have been based on acts descriptive and / or prescriptive use without great value in the training of communication skills. The collection Cadernos de apoio e aprendizagem, aimed at elementary school students and produced in partnership ( Secretaria Municipal de Educação de São Paulo and Fundação Padre Anchieta ) , is the result of educational politics in Brazil . In context, justified quest for emancipatory curriculum, enhancing education for democratic practice and contextualizes the question that animates this study: The collection of books is a support and learning curriculum with emancipatory character ? Study focused on the issue of quality of education, often only measured by the results of large-scale assessments. There is an inversion, since the evaluation, taken as a promoter of quality, legitimate control of the teaching-learning process and becomes determinant of curriculum politics. Also the official documents prescribe directions for educational work. Two documents are analyzed to detect the degree of determination: Parâmetros Curriculares Nacionais e Orientações Curriculares e Expectativas de Aprendizagem. Besides them, a query to the Bank of CAPES thesis allowed the recovery of 115 documents and examining subsidies offered to understand the degree of determination that cut production in academic concepts and actions related to language teaching. The notes of support and learning were taken to verify their adherence to the requirements and academic officers and their potential as emancipatory curriculum. The collection was also considered from the student's record and the evidence of the teacher's pedagogical action. It was discovered that potential, but also weaknesses that suggest limitations on its scope as curriculum and on its emancipatory character. Thus, although valuable, the initiative arises only as a didactic material available